Heritage reclamation: focusing on Negeri Sembilan’s Minangkabau cultural landscape - Mohd Hussain, Mohd Ramzi; Md Jani, Haza Hanurhaza; Tukiman, Izawati; Abu Samah, Mohd Armi (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The focus of this paper is to examine the importance of cultural landscape reclamation, as well as historical values with which historical occurrences and incidences are associated. The study strives to gain insights from traditional cultural values and the importance of their reclamation in society. Indeed, most of the historical occurrences emerge as human legacies because different generations interact with the perceived heritage traditions and values. As such, cultural landscape reclamation refer to a practice of regaining human legacy’s valuable heritage, with the latter reflecting the original culture and identity of a given community or place – but destroyed at some point. Therefore, the objective of the current study is to examine the reclamation of a cultural landscape in Negeri Sembilan’s Minangkabau, as well as establish some of the feasible strategies that could be implemented to ensure that the traditions are protected; besides shielding the identity and local practices from being eroded. Indeed, the study adopts qualitative research, with a survey technique used to collect data via the administration of questionnaires. From the results, it is evident that the decision to define a community’s identity is critical because it preserves its traditions. Also, identity is seen to aid in the characterization and distinguishing of a given community from the rest of society. The eventuality is that the preservation of a group’s traditions needs to be preceded by addressing local identity, a trend achieved through landscape reclamation.